2022
DOI: 10.1590/0102-311xen234421
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vulnerability among Brazilian sexual and gender minorities: a cross-sectional study

Abstract: Minority groups are more prone to worsen their personal and social vulnerabilities during the COVID-19 pandemic. This study aimed to identify factors associated with the highest COVID-19 vulnerability in the Brazilian sexual and gender minorities. This is a cross-sectional study based on 826 respondents of the Brazilian LGBT+ Health Survey, conducted online from August to November 2020. The COVID-19 vulnerability was based on a previous vulnerability index created by an LGBT+ institution, which comprises three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
0
10
0
3
Order By: Relevance
“…Out of the 13 original research studies identified in this review, eight (8) collected primary data [23,35,37,38,49,54,56,57], four (4) relied exclusively on secondary data [24][25][26]34], and one (1) combined secondary and primary data [45]. None of the identified publications intended to demonstrate the existence of a particular syndemic; instead, they used syndemic theory as an interpretative lens (an approach, a theory, a concept, or a framework) to conceptualize and analyse emerging data.…”
Section: Which Methodological Approaches Were Used To Describe These ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the 13 original research studies identified in this review, eight (8) collected primary data [23,35,37,38,49,54,56,57], four (4) relied exclusively on secondary data [24][25][26]34], and one (1) combined secondary and primary data [45]. None of the identified publications intended to demonstrate the existence of a particular syndemic; instead, they used syndemic theory as an interpretative lens (an approach, a theory, a concept, or a framework) to conceptualize and analyse emerging data.…”
Section: Which Methodological Approaches Were Used To Describe These ...mentioning
confidence: 99%
“…Finally, gender-differentiated impacts of COVID-19 were studied by Neto et al [56] and Duby et al [57]. The former [56] argued that COVID-19 could have been experienced as a syndemic by gender and sexual minorities in Brazil due to various forms of vulnerability they have historically faced, including racial and gender discrimination, low education levels, precarious working conditions, and reliance on social support systems. The latter [57] took a similar approach to study the impacts of COVID-19 on adolescents, girls, and young women (AGYW) in six districts in South Africa.…”
Section: Impacts Of Covid-19 On Specific Populationsmentioning
confidence: 99%
“…No âmbito da saúde, o cenário gerado pela rápida disseminação do novo coronavírus, somado à demora de iniciativas governamentais e ao contexto de estigmatização da população LGBTQIAPN+, gerou ainda mais dificuldades para o acesso à saúde, principalmente para aqueles que vivem e dependem do Sistema Único de Saúde para o tratamento de IST, deixando necessidades específicas em segundo plano 29 .…”
Section: Vulnerabilidade No Contexto Da Pandemia De Covid-19unclassified
“…En el ámbito de la salud, el escenario generado por la rápida propagación del nuevo coronavirus, sumado al retraso en las iniciativas gubernamentales y al contexto de estigmatización de la población LGBTQIAPN+, generó aún más dificultades en el acceso a la salud, sobre todo para quienes viven y dependen del Sistema Único de Salud para el tratamiento ITS, dejando en un segundo plano las necesidades específicas 29 .…”
Section: Vulnerabilidad En El Contexto De La Pandemia De Covid-19unclassified